Chronic diseases of lifestyle: A risk assessment and health promotion framework for a rural and urban primary health care setting in the Free State province, South Africa - van Zyl, Sanet; Kruger, Willem H.; Walsh, Corinna M. (MDPI, 2024)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱: Non-communicable diseases (NCDs) are the leading cause of global mortality. The WHO projects a rise in NCD-related deaths from 36 million in 2018 to 55 million by 2030, with developing countries being the most affected. Effective community-based primary health care (PHC) can reduce the burden of chronic diseases of lifestyle (CDLs). This study aimed to develop a risk assessment and health promotion framework to strengthen CDL prevention and control in Free State (FS) communities in South Africa. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀: A convergent mixed-method design was used. Quantitative analysis identified CDL risk factors in rural and urban FS settings, while qualitative focus group discussions explored participants’ knowledge of CDLs and their experiences with program implementation. 𝗥𝗲𝘀𝘂𝗹𝘁𝘀: Key findings highlighted differences in risk profiles, CDL training needs for PHC teams, patient education gaps, and curriculum development. Step 1 of the framework development identified differences and similarities in the CDL risk profiles of the study populations. Step 2 identified CDL training needs for PHC teams, patient educational needs, and CDL curriculum development needs. Step 3 revealed three main barriers: resource constraints, patient non-compliance, and the lack of supporting healthcare services. In Step 4, the six focus areas identified (steps 1–3) were used to develop strategies for implementing a tailored, community-based, patient-centred approach. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻𝘀: The results provide valuable insights for improving PHC responses in resource-limited settings.
Keywords: Chronic diseases of lifestyle; Primary health care; Risk assessment; Community-based education; CDL intervention programs